Sleep habits and sleep disorders in beverage factory shift workers - DURAND, GERARDO (2004)
Objective:To determine frequency, habits and sleep disorders in shift worker subjects. Design: Observational, descriptive and cross sectional study done in october 2001. Material and Methods: A previous validated, volunteer and self filled questionnaire was used; 88 (22%) workers participated in the study; age x=42±7,4 [23-65] years; 47,7% had 8 hours of shift work (SW) and the difference were regular workers (RW); 8% were women. Results: Sleep length was x=6,7±1 [4-10] hours. SW slept 30 minutes more than RW; 50% of RW and 38% of SW slept ≤6 h/d (NS), 11% of RW and 31% of SW slept ≥8 h/d (p<0,05); 62% of RW and 61% of SW suffered of insomnia; 75% of SW and 61% of RW who slept ≤6 h/d showed insomnia (NS). Nineteen (49%) who slept ≤6h and thirteen (27%) who slept >6h showed somnolence during work (p<0,05). Twenty one (49%) RW and fifteen (32%) SW who drove revealed they «dozed off» at least in one opportunity while driving (p=0,1); six (15%) RW had an accident because of this reason; 48% of SW and 33% of RW did not have a regular sleep-awake cycle; 47% of RW and 30% of SW showed somnolence during work (NS). Conclusions: High percentage of workers (SW and RW) did not sleep enough and showed insomnia and somnolence. RW were awake during the night more frequently and reported significant more snoring than SW. Nevertheless, SW who snore reported more pauses in their breathing. The need for further studies with larger samples is emphasized.